Forecasting the governance of harmful social media communications: findings from the digital wildfire policy Delphi. (2nd January 2021) - Edwards, Adam; Webb, Helena; Housley, William; Beneito-Montagut, Roser; Procter, Rob; Jirotka, Marina
ABSTRACT : Social media exhibits the core characteristics of emergent technologies. It is disruptive of established ways of organising social relations, is evolving at an exponential pace and its effects, including the production of new 'goods' and 'bads', are highly uncertain. Interest in understanding these effects has intensified in the context of fears over so-called 'digital wildfire', a policy construct referring to rapid propagation of harmful communications, particularly those involving children and other vulnerable social groups but also those threatening the integrity of the political process in liberal democracies. Even so, proponents of social media are anxious to protect its potential for enhancing freedom of speech and revitalising civil society through the redistribution of editorial powers to shape public debate and facilitate the democratic scrutiny and oversight of elites. This article reports findings of the 'Digital Wildfire policy Delphi', which asked key informants to consider the political and technical feasibility of regulating harmful social media communications and to forecast likely scenarios for their prospective governance. Key forecasts are that forms of enforcement are limited, stimulating 'self-regulation' will become increasingly important but, more controversially, the likelihood is that harm to vulnerable groups will be 'accommodated' in liberal democracies as a price to be paid for the perceived political and economic benefits of unmoderated social media. The article concludes with conjectures about future directions in the policing of social media and their implications for shaping the emerging research agenda.